1992
DOI: 10.1073/pnas.89.23.11466
|View full text |Cite
|
Sign up to set email alerts
|

Methodologic aspects of a population pharmacodynamic model for cognitive effects in Alzheimer patients treated with tacrine.

Abstract: Tacrine is a cholinesterase inhibitor with activity in the central nervous system originafly marketed for the reversal ofcompetitive neuromuscular blockade. Because a marked reduction in cholinergic neurons is a halr of brain changes in Alzhelmer disease, tacrine has been studied in two placebo-controlled clinical trials of patients with probable Alzhelmer disease. (6) and protocol 970-04 (7). Analysis ofthe double-blind phase of the 970-01 trial led to the conclusion that there was a significant difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 9 publications
0
57
0
Order By: Relevance
“…The tumor effect compartment half-life can be thought of as being the apparent elimination half-life of drug from the system after a hypothetical bolus input at the time of each gemcitabine dose (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…The tumor effect compartment half-life can be thought of as being the apparent elimination half-life of drug from the system after a hypothetical bolus input at the time of each gemcitabine dose (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…By the successful prediction of the 14-week trial, the implementation in the models seems to be justified. A published placebo model (34) could not be applied for parameter estimation probably due to the sparse data situation. Fixing the parameters to literature values and applying them to the 4-week study data showed satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the sparse data situation, parameters of the model could not be estimated. Subsequently, all structural and IIV parameters were fixed to literature values (34). Population and individual predictions were obtained by setting the number of evaluations to 0 (MAXEVAL=0).…”
Section: Disease Progression and Placebo Effect Modelmentioning
confidence: 99%
“…A linear model assumes that a disease status deteriorates at a constant rate over time. It was used for example in describing the natural course of Alzheimer's disease (21) and the glycemic deterioration associated with type II diabetes mellitus (22). In cases where there is a natural limit for disease progression, an asymptotic model is used.…”
Section: Disease Progression Modelingmentioning
confidence: 99%